Multiple endovascular stent-graft implantations in a patient with aortic thoracic and abdominal aneurysms due Takayasu arteritis. (2014)
We report an adult female patient with Takayasu arteritis (TA) receiving conventional medical treatment and anti-TNF therapy, which developed progressive thoracic and abdominal aortic aneurysms. She developed imminent rupture of the thoracic aneurysm and an endovascular stent-graft (EVSG) was emergency implanted and a year after this procedure the abdominal aneurysm increased in size requiring reoperation and placement of another EVSG. Both procedures had a very good outcome. This case shows the effectivity and security of multiple EVSG implantations in multiple aortic aneurisms in patients with TA.